Poststernotomy Osteomyelitis Presenting with Severe Sepsis and Rhabdomyolysis - Eugene M. Tan; Melissa Lyle; Kelly Cawcutt; Zelalem Temesgen (Case Reports in Medicine)
A 39-year-old male, who recently underwent a composite valve graft of the aortic root and ascending aorta for bicuspid aortic valve and aortic root aneurysm, was hospitalized for severe sepsis, rhabdomyolysis (creatine kinase 29000 U/L), and severe liver dysfunction (AST > 7000 U/L, ALT 4228 U/L, and INR > 10). Cardiac magnetic resonance imaging (MRI) findings were consistent with sternal osteomyelitis with a 1.5 cm abscess at the inferior sternotomy margin, which was contiguous with pericardial thickening. Aspiration and culture of this abscess did not yield any organisms, so he was treated with vancomycin and cefepime empirically for 4 weeks. Because this patient was improving clinically on antibiotics and did not show external signs of wound infection, there was no compelling indication for sternectomy. This patient’s unusual presentation with osteomyelitis and rhabdomyolysis has never been reported and is crucial for clinicians to recognize in order to prevent delays in diagnosis.